"Whatever it takes!": How tonality of TV-news affects government bond yield spreads during crises - Patrick Hirsch; Ekkehard A. Köhler; Lars P. Feld; Tobias Thomas (Albert-Ludwigs-Universität Freiburg, Institut für Allgemeine Wirtschaftsforschung, Abteilung für Wirtschaftspolitik und Ordnungsökonomik, 2020)
Are government bond risk premia affected by TV news in addition to the effect of the original event reported? We analyze 1,209,566 human-coded news items from newscasts aired by leading TV stations in Europe and the US between January 2007 and November 2016. We establish causality using instrumental variables that attract media attention and crowd out media coverage on Eurozone related news. We find FIFA and UEFA tournaments as well as major natural disasters and airplane crashes as valid instruments for the empirical analysis. The results show that an exogenous variation in the share of Eurozone related news affects bond spreads. A one percentage point increase in the share of Eurozone related news leads to -7.6 basis points lower bond spreads. Taking the tonality of the news into account paints a more differentiated picture: A one percent higher share of positive Eurozone related news leads to -69.7 basis points lower bond spreads, whereas a one percentage point higher share of negative country-specific news is related to 2.5 basis points higher bond spreads.
Keywords: E58; G12; L82; 330; Media bias; TV Newscasts; Tonality; Eurozone crisis; GIIPS bond yield spreads